1999
DOI: 10.1128/aem.65.4.1772-1776.1999
|View full text |Cite
|
Sign up to set email alerts
|

Diversity ofBacteroides fragilisStrains in Their Capacity To Recover Phages from Human and Animal Wastes and from Fecally Polluted Wastewater

Abstract: Great differences in capability to detect bacteriophages from urban sewage of the area of Barcelona existed among 115 strains ofBacteroides fragilis. The capability of six of the strains to detect phages in a variety of feces and wastewater was studied. Strains HSP40 and RYC4023 detected similar numbers of phages in urban sewage and did not detect phages in animal feces. The other four strains detected phages in the feces of different animal species and in wastewater of both human and animal origin. Strain RYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 32 publications
0
28
0
7
Order By: Relevance
“…Bacteroides fragilis RYC2056 (ATCC700786) (Puig et al, 1999) and B. thetaiotaomicron GA17 (Payán et al, 2005) were used as host strains for phage detection in this study. Strain RYC2056 does not discriminate between faecal sources and was used as a control, while strain GA17 is specific for the detection of phages from human faecal sources.…”
Section: Strains and Bacteriophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteroides fragilis RYC2056 (ATCC700786) (Puig et al, 1999) and B. thetaiotaomicron GA17 (Payán et al, 2005) were used as host strains for phage detection in this study. Strain RYC2056 does not discriminate between faecal sources and was used as a control, while strain GA17 is specific for the detection of phages from human faecal sources.…”
Section: Strains and Bacteriophagesmentioning
confidence: 99%
“…Among these methods, bacteriophages that infect Bacteroides are potential tools for MST (Tartera et al, 1989;Grabow et al, 1995;Puig et al, 1999;Blanch et al, 2006). Bacteroides host strains vary in their capacity to discriminate between phages from different sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiological methods include: ratios of faecal coliforms to faecal streptococci (Geldreich and Kenner 1969); the presence of Rhodococcus coprophilus (Mara and Oragui 1981); the presence of some phenotypes of Bifidobacterium species (Mara and Oragui 1983); the presence of some phenotypes of Bacteroides species (Kreader 1995); ribotypes of Escherichia coli (Carson et al 2001;Parveen et al 1999); repetitive DNA sequences of E. coli (Dombek et al 2000); antibiotic resistance patterns (Wiggins 1996;Harwood et al 2000); serogrouping of F-specific RNA (F-RNA) bacteriophages (Furuse et al 1978); bacteriophages specific for various strains of Bacteroides fragilis (Tartera et al 1989;Puig et al 1999) and phage typing of Staphylococcus aureus (Zierdt et al 1980). The ideal would be to have a single test to determine the origin of faecal pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this instance the coliphage removals are more similar to human virus (adenovirus, rotavirus and enterovirus) removal than E. coli or bacterial pathogen removal for many treatments. Phage infecting Bacteroides rank third in abundance in raw wastewater after SC and F-RNA phage (Tartera and Jofre, 1987;Tartera et al, 1989;Lucena et al, 1994;Ebdon et al, 2007;Edbon et al,2012) and their ratio with respect to SC and F-RNA phages has been shown to be remarkably constant (Puig et al, 1999;Contreras-Coll et al, 2002;Lucena et al, 2003;Blanch et al, 2004;Jofre et al, 2007). Most Bacteroides phages have a very narrow host range (Lucena and Jofre, 2010).…”
Section: Coliphage (Somatic and F-rna)mentioning
confidence: 99%